OxyR-regulated catalase CatB promotes the virulence in rice via detoxifying hydrogen peroxide in Xanthomonas oryzae pv. oryzae. Issue 1 (December 2016) - Yu, Chao; Wang, Nu; Wu, Maosen; Tian, Fang; Chen, Huamin; Yang, Fenghuan; Yuan, Xiaochen; Yang, Ching-Hong; He, Chenyang
Abstract Background To facilitate infection, Xanthomonas oryzae pv.oryzae (Xoo ), the bacterial blight pathogen of rice, needs to degrade hydrogen peroxide (H2 O2 ) generated by the host defense response via a mechanism that is mediated by the transcriptional regulator OxyR. The catalase (CAT) genecatB has previously been shown to belong to the OxyR regulon inXoo . However, its expression patterns and function in H2 O2 detoxification and bacterial pathogenicity on rice remain to be elucidated. Results ThecatB gene encodes a putative catalase and is highly conserved in the sequenced strains ofXanthomonas spp. β-galactosidase analysis and electrophoretic mobility shift assays (EMSA) showed that OxyR positively regulated the transcription ofcatB by directly binding to its promoter region. The quantitative real-time PCR (qRT-PCR) assays revealed that the expression levels ofcatB andoxyR were significantly induced by H2 O2 . Deletion ofcatB oroxyR drastically impaired bacterial viability in the presence of extracellular H2 O2 and reduced CAT activity, demonstrating that CatB and OxyR contribute to H2 O2 detoxification inXoo . In addition, ΔcatB and ΔoxyR displayed shorter bacterial blight lesions and reduced bacterial growth in rice compared to the wild-type stain, indicating that CatB and OxyR play essential roles in the virulence ofXoo . Conclusions Transcription ofcatB is enhanced by OxyR in response to exogenous H2 O2 . CatB functions as an active catalase that is required for the full virulence ofXoo in rice.